Relational Reading~Writing~Thinking~Becoming in Higher Education: Possibilities for scholarly reading and writing in times of turbulence - Verster, Belinda; van den Berg, Carolien; Collett, Karen (Critical Studies in Teaching and Learning, 2024)
The paper explores our scholarly practice of collaborative academic writing by engaging with a Relational Reading of Text approach and Slow scholarship. It grew out of our need to explore the tensions and inertia in our collaborative writing before, during, and after the COVID-19 lockdown, to find our way back to flourishing and thriving through each other. We draw on the relational reading~writing~thinking~becoming dimensions of ‘sense of movement’, ‘shifts to the in-between spaces of meaning’, ‘the quality of kindred’, and ‘shared responsibility’. A collaborative autoethnographic approach was used in relation to the notion of diffraction. We conceptualise a ‘pandemic-transformed’ approach for us to not only survive the digital turn our co-writing practices have taken but to find our way back to an authentic, creative, and joyful engagement. Insights may be of value to other academics who seek to co-write in ways that support flourishing and Slow scholarship in higher education.